Eficacia de la observación microscópica directa y el cultivo en el diagnóstco de las dermatofitosis en caninos - Reinoso, EH. (2017)
Dermatophytosis (ringworm) are superficial mycosis produced by molds with strong keratinophilic activity, affecting skin of humans and animals. Pets have a special role, because they are one of the most common sources of infection for men, particularly children because of their close relationship with them. The confirmation of these diseases is through mycology laboratory diagnosis, where the performance (positivity) of laboratory parameters in human samples is much higher compare to samples of animal origin. Diagnostic confirmation in ringworm of children exceeds 90%; while in animals with compatible clinical forms of this mycosis, only a minor percentage is confirm by the laboratory. The maximum isolation values of fungi that cause dermatophytosis in dogs are 36.9 - 40%. Our objective is to determine the laboratory performance in samples of skin and hair of canines with clinical suspicion of superficial mycoses from the City of La Plata, between March 2005 and March 2013, using the classic techniques of direct microscopic observation and culture.\n